The world's most notorious Greek - Ashenden, Jackie (Harlequin presents, 2021)
"To defy the father who refused to acknowledge him and gain his rightful inheritance, Achilles Templeton must wed and have a son. For a famous playboy like him, such conditions seem impossible. Until he meets the perfect bride right next door... Innocent Willow Hall has exhausted her spirit-and bank account-caring for a father who never truly loved her. Achilles's proposition is an outlandish lifeline! But it's not the terms of their convenient marriage that scare her...It's the all-consuming fire Achilles unleashes within her!"--